Pengaruh Penerapan Model Kooperatif Tipe Talking Stick Terhadap Hasil Belajar PAI Siswa Kelas V SDN 12 Padang Lua - Sherlia Salsabilla; Darul Ilmi; Afrinaldi Afrinaldi; Deswalantri Deswalantri (Guruku: Jurnal Pendidikan dan Sosial Humaniora, 2023)
This research was raised and the problems fthat research found in class V SDN 12 Padang Lua were that there were low students islamic education learning outcomes. This can be seen in the students’ MID scores, where there are still many student who have not achieved completeness, which is 75. This study aims to see whether the talking stick type cooperative learning model can affect student learning outcomes, especially in the subject of Islamic Religious Education at SDN 12 Padang Lua. In this study, the research used a quasi-experimental design and nonequivalent control group design. Based on the research result and hypothesis testing, it shows that the learning model, namely the cooperative talking stick type, has an effect on students learning outcomes in PAI subject for fifth grade student of class V at SDN 12 Padang Lua. In determination coefficient test, a value of 71,9% is influenced by the talking stick and cooperative learning model 28,1% influenced by other aspects not examined. Then in testing the hypothesis using the parametric test, test Sig. value is 0,033, where the value is Sig. 0,033 < 0,05. Therefore it was So it concluded that there was a significant influence on learning outcomes after the cooperative learning model was applied to the talking stick type in Islamic Religious Education subjects. This means that Ho is rejected and Ha is accepted (hypothesis accepted).